Kindergarten teachers practice in Hafar Al-Batin for active learning strategies - Aljurbua, Ghada Ahmed (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the most important strategies for children's learning and their common education from the point of view of early childhood teachers. The study used the descriptive approach. An electronic questionnaire was applied to a sample of "280" early childhood teachers in the city of Hafar Al-Batin. One of the most important results of the study was that the kindergarten teacher used the active learning strategy. It came in average. And there are no statistically significant differences between the kindergarten teacher's use of active learning strategies for children, depending on the school type variable between public and private schools. The study recommended the need to provide material capabilities and appropriate conditions that help the teacher to employ active learning strategies. And holding courses and workshops that develop the ability of teachers to employ active learning.
Keywords: Learning and Education Strategies; Kindergarten; Kindergarten Teacher